(untitled) (Dhaka University Journal of Science, 2022)
In this study, a hydrogel composite based on natural jute fiber (JF) has been prepared and employed for the removal of methylene blue (MB) dye from aqueous solution. Polyacrylamide (PAAm) hydrogel was synthesized by thermal polymerization in presence of N,N□-methylene bisacrylamide (MBAA) as the cross-linker and potassium per sulfate (KPS) as the initiator. JF reinforced hydrogel (JFRH) composite was prepared by incorporating JF into PAAm matrix prior to the polymerization. The prepared JFRH was characterized by FTIR spectroscopy and scanning electron microscope. It was found that, JFRH composite demonstrated strong mechanical properties with a compressive strength of 1.5 MPa at a deformation of above 80%. The prepared JFRH composite can remove more than 90% of MB from an aqueous solution and be separated easily from the solution after the adsorption process. Therefore, the synthesized JF based hydrogel composite could significantly expand the use of our natural golden fiber for reinforcement of composite materials and removal of dyes from water bodies. Dhaka Univ. J. Sci. 70(2): 59-64, 2022 (July)